2020
DOI: 10.3389/fpubh.2020.00354
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Task and Break Timing to Reduce Ultraviolet Radiation Exposure in Outdoor Workers

Abstract: Objectives: Public health messaging about sun avoidance strategies is often not practical for outdoor workers. The objective of this study was to use personal monitoring data to determine when peak UVR exposure occurs for outdoor workers, estimate how much UVR could be reduced by altering the timing of shady tasks or breaks during peak exposure times, and descriptively compare these to peak periods of ambient UVR. Ultimately, we aim to provide evidence-based sun avoidance recommendations for outdoor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In another study, as an important contribution, the authors suggested that sun exposure could be reduced substantially by implementing rational, strategic interruptions to the working day. If performed optimally, this approach could achieve a reduction of 0.18 SED per hour, a total of 15.9% less sun exposure during the day 29…”
Section: Discussionmentioning
confidence: 99%
“…In another study, as an important contribution, the authors suggested that sun exposure could be reduced substantially by implementing rational, strategic interruptions to the working day. If performed optimally, this approach could achieve a reduction of 0.18 SED per hour, a total of 15.9% less sun exposure during the day 29…”
Section: Discussionmentioning
confidence: 99%
“…Patients were categorized into four groups based on skin disease: (1) skin cancer, actinic keratosis, and/or other precancerous skin diseases, (2) hyperpigmentary skin disorders such as melasma, freckle, and lentigo, (3) hypopigmentary skin disorders such as vitiligo, and (4) other and unspecified skin diseases such as acne, seborrheic dermatitis, or keloid. This categorization was based on diseases expected to be most significantly affected by UV radiation (skin cancer, hyperpigmentary skin disorders, and hypopigmentary skin disorders), including those with insufficient evidence of association with UV radiation (other and unspecified skin diseases) 1–9,21 . Patients who could not understand or answer the questionnaire due to their education level were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…3,5 Studies have shown that these diseases are more prevalent in outdoor workers, occur more frequently in whites, and are more common in the face, an area of high exposure to sunlight. 6,7 In addition, hyperpigmentary disorders, such as melasma, freckles, and lentigines, are mainly attributed to sun exposure. 8 Although the exact cause of hypopigmentation disorders, such as vitiligo, is not clear, external stimuli such as UV radiation are known to be involved in melanocyte destruction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 Providing shaded areas for breaks and task rotation/flexibility during peak UVR hours may be more effective than relying on personal protective behaviours. 31 There is also no good evidence as to the effectiveness of these approaches in preventing skin cancer. For example, Sanchez et al .…”
Section: Workplace Exposure To Uv Radiation and Risk Managementmentioning
confidence: 99%